Consumer-based optimization and standardization of bottled tomato-guapple jam - Narag, Jemie Rose Ma. Theresa Talosig; Villarino, Blanca J. (2009 ; Blanca J. Villarino)
ABSTRACT The study aimed to develop an acceptable bottled tomato-guapple jam through consumer-based optimization and standardization procedures. The most acceptable tomato-guapple jam production method determined in the preliminary phase was used to develop an optimum tomato-guapple jam formulation through mixture response surface methodology (RSM). Independent variables used in the RSM and their corresponding ranges were 16.50 - 41.25% tomato puree, 8.25 - 27.50% guapple puree, and 45.00 - 67.00% sugar. Responses evaluated were the acceptance of the sensory attributes of the jam. A determined optimum tomato-guapple jam formulation was further verified and standardized. Optimized tomato-guapple jam was subsequently hot-filled into 8 oz glass jars. Results of the RSM showed that puree-sugar mixtures containing 24.0 - 30.1% tomato puree, 21.5 - 26.5% guapple puree, and 47.0 - 51.7% sugar, acidified with calamansi extract to a pH of around 3.1 before cooking, yielded acceptable products. Verification of the prediction models for an acceptable formulation indicated that the models are valid and reproducible. Furthermore, results of standardization experiment of the optimized formulation signified that it is repeatable. Results of the physico-chemical, microbial and consumer acceptance tests of the hot-filled optimized tomato-guapple jam implied that hot-filling is an adequate technique technique to make the ultimate product safe and acceptable. Specifically, the final product yielded in the study had a mean pH level of 3.12 and soluble acids level of 66 Brix. It was composed of 27.50% tomato puree, 22.65% guapple puree, 49.85% sugar and enough calamansi extract to make the pH level prior to cooking around 3.1.
Thesis (BSFT) -- University of the Philippines Diliman
Keywords: Jam; Fruit -- Preservation -- Philippines